2017
DOI: 10.2174/0929867324666170303162416
|View full text |Cite
|
Sign up to set email alerts
|

Family B G Protein-coupled Receptors and their Ligands: From Structure to Function

Abstract: The findings of this review provide information about the structural-functional determinants of family B GPCRs and their ligands, thus boosting the design of novel drugs with better potencies and bioavailabilities, which might enrich the therapeutic armory for the treatment of a wide spectrum of family B GPCRs-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…The B1 subfamily is made of largely classical hormone receptors. It comprises three types of hormone receptors in D. melanogaster: diuretic hormone 31 receptor (DH31-R/hector), CRF-like diuretic hormone 44 (DH44-R), and pigment dispersing factor receptor (Pdfr) (57)(58)(59)(60). In our study, all three types of hormone receptors were identified.…”
Section: Family-b Gpcrsmentioning
confidence: 71%
“…The B1 subfamily is made of largely classical hormone receptors. It comprises three types of hormone receptors in D. melanogaster: diuretic hormone 31 receptor (DH31-R/hector), CRF-like diuretic hormone 44 (DH44-R), and pigment dispersing factor receptor (Pdfr) (57)(58)(59)(60). In our study, all three types of hormone receptors were identified.…”
Section: Family-b Gpcrsmentioning
confidence: 71%
“…As is the case for all GPCRs, the GLP-1R consists of an extracellular N-terminal domain (N-domain), an intracellular C-terminal region, and seven TMs that are connected to each other by three extracellular loops (ELs) and also three intracellular loops (10,69). The ELs and TMs form the J-domain of receptor that binds GLP-1.…”
Section: Computational Modeling Predicts Conserved Features Of Ligandmentioning
confidence: 99%
“…Of the 826 human GPCRs, 118 are recognized as endogenous peptide or protein ligands. 10 To date, besides the class B structures binding to α-helical peptides, 11 only a few published crystal structures of class A GPCRs bound to peptides including the neurotensin receptor 1 (NTSR1) bound to NTS, 12 the chemokine receptor CXCR4 in complex with a cyclic peptide agonist 13 and a viral chemokine, 14 and the angiotensin II type 2 receptor bound to an angiotensin II analogue. 15 However, there is no conserved structural information of peptides binding to GPCRs because of their diversity in sequence, size, and conformation.…”
Section: Introductionmentioning
confidence: 99%